BAQIR AL-SADR AND THE FOUNDATIONS OF ISLAMIC ECONOMICS AS AN IDEOLOGICAL SCHOOL OF THOUGHT: A REFLECTIVE INTERPRETATION THROUGH WILHELM DILTHEY’S HERMENEUTICS - Lazuardi Annas, Muhammad (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze Muhammad Baqir al-Sadr's economic system of thought, particularly in developing a distinctive conceptual framework for Islamic economics based on sharia principles. The type of research used is qualitative with a case study approach, which serves to gain an in-depth understanding of al-Shadr's ideas, concepts, and contributions to Islamic economics. Secondary data was obtained through a literature study of al-Sadr's main work, Iqtishaduna, and analyzed using descriptive-analytical methods with Wilhelm Dilthey's hermeneutic theoretical framework. The findings show that al-Shadr defines Islamic economics as an ideological school of thought and normative doctrine that is fully integrated into the structure of Islamic teachings, not merely an empirical science. The system he built is based on three main pillars: dual ownership (private and public), economic freedom limited by sharia, and the enforcement of social justice principles, which are realized through takaful ijtima‘i and tawazun ijtima‘i. Al-Shadr rejected the views of Capitalism and Marxism on economic issues, stating that the real root of economic problems lies in human greed and unfair distribution, not in the scarcity of resources. Methodologically, his criticism of Historical Materialism is understood as a rejection of attempts to apply the reductionist Erklären (explanatory) method to the human sciences. Finally, Al-Sadr's process of Iktishāf (discovery) of Islamic economic theory—which moves from legal details (furū) to general theoretical principles (al-qā’idah al-‘āmmah)—is in line with Dilthey's concept of Seminal Decision as a methodological reconstruction to reveal the systematic coherence of Sharia.